1968
DOI: 10.1037/h0026530
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde amnesia produced by hypothermia in rats.

Abstract: In Experiment 1, rats received escapable shock upon crossing into the black side of a black-white chamber. The Ss receiving hypothermia 20 sec., 5 min., or 15 min. after the single training trial showed significantly poorer 24-hr, retention of the passive avoidance response than 60-min. delay or control Ss. In Experiment 2, severity of hypothermia was varied for groups receiving a passive avoidance training trial with inescapable shock. Cooling & to body temperatures below 75° F. resulted in retrograde amnesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

1968
1968
2002
2002

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 14 publications
4
47
0
Order By: Relevance
“…Similar results have been obtained with many of the amnesic agents (e.g., Hinderliter et al, 1976). Furthermore, the results of Experiment 2a indicate that the memory loss produced by hyperthermia resembles that produced by other amnesic agents inasmuch as there is a direct relationship between the amount of memory loss and the severity of the hyperthermal treatment, a relationship characteristic of agents such as ECS (Weissman, 1964) and hypothermia (Riccio et al, 1968). Finally, the results of Experiment 3 indicate that, on empirical grounds, the memory loss produced by hyperthermia resembles that produced by other amnesic agents inasmuch as hyperthermia also selectively impairs recent memory.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Similar results have been obtained with many of the amnesic agents (e.g., Hinderliter et al, 1976). Furthermore, the results of Experiment 2a indicate that the memory loss produced by hyperthermia resembles that produced by other amnesic agents inasmuch as there is a direct relationship between the amount of memory loss and the severity of the hyperthermal treatment, a relationship characteristic of agents such as ECS (Weissman, 1964) and hypothermia (Riccio et al, 1968). Finally, the results of Experiment 3 indicate that, on empirical grounds, the memory loss produced by hyperthermia resembles that produced by other amnesic agents inasmuch as hyperthermia also selectively impairs recent memory.…”
Section: Discussionsupporting
confidence: 70%
“…The left panel of Figure 2 shows the mean step-down latency during training and the right panel the mean step-down latency during testing. An analysis of variance performed on the training data yielded no significant group differences [F(5,54) (Paolino, Quartermain, & Miller, 1966;Riccio et al ., 1968). If a similarity between the amnesias produced by hyperthermia and other agents is to be established then it must be shown that hyperthermia also has a selective effect on recent memory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ohio 44242. acquisition of the passive avoidance task is reported to vary with age (Riccio, Rohrbaugh, & Hodges, 1968), these differences appear minimal beyond 2S days of age. Hypothermia was chosen as the amnestic agent, partly because of its demonstrated effectiveness in producing memory loss (e.g., Beitel & Porter, 1968;Misanin et aI., 1971;Riccio, Hodges, & Randall, 1968) and partly because the severity of treatment could be readily indexed in terms of colonic temperature change'. It was hoped that the functional intensity of the amnestic agent could be roughly matched for both age groups by equating the extent of body temperature loss (cf.…”
mentioning
confidence: 99%
“…As explained traditionally by the concept of memory consolidation, RA results from a failure of memory storage (see, e.g., Jacobs & Sorenson, 1969;Riccio, Hodges, & Randall, 1968;Spanis & Squire, 1987), and it has been thought by many researchers to be permanent (e.g., King & Glasser, 1970;Luttges & McGaugh, 1967). However, increasing numbers of studies continue to demonstrate that animals are able to recover memories thought to be lost permanently due to the amnesic treatment (see Riccio & Richardson , 1984, for a review).…”
Section: Hypothermia-induced Retrograde Amnesia In Young and Adult Swmentioning
confidence: 99%